Hygrothermal aging on the mechanical property and degradation mechanism of carbon fiber reinforced epoxy composites modified by nylon 6 - Guijun Xian; Yanbo Bai; Xiao Qi; Jianling Wang; Jingwei Tian; Huigang Xiao (Journal of Materials Research and Technology)
Nylon 6 (PA6) with excellent fracture toughness and hygrothermal resistance is added to the high-strength/modulus carbon fiber reinforced epoxy resin as a filler, which is expected to signally improve the thermal and mechanical properties. In the present paper, epoxy resin was reinforced by short carbon fibers and PA6 fillers of different content, and nylon 6 modified carbon fiber-epoxy resin (PA6CFEP) composite was successfully prepared. Water absorption behavior, thermal and mechanical performance evolution, degradation mechanism, as well as micro-structure and micro-morphology analysis of PA6CFEP before and after hygrothermal aging at 20/40/60 °C for 120 days were discussed and analyzed. The results showed that the water absorption law of PA6CFEP immersed in water solution accorded with the modified Fick's diffusion model, and the quasi-equilibrium water absorption (M∞) was 3.49%. Additionally, the maximum water absorption (Mmax) and diffusion coefficient (D) of the sample at 60 °C increased by 45.98% and 6.39% compared with those at 20 °C. Based on the optimal PA6 content (7.5 wt%), the fracture toughness of PA6CFEP-7.5 was 198.6% higher than that of the control sample, which was an increase in tensile strength (34.0%) and elongation at break (77.3%). Furthermore, the PA6 addition increased the Tg of PA6CFEP by a maximum percentage of 4.9%, which indicated that PA6 had excellent thermodynamic compatibility with the epoxy resin. After hygrothermal aging of PA6CFEP-7.5 for 120 days at 60 °C, the tensile strength, bending strength and Tg decreased by 36.5%, 38.3% and 16.9% compared to the control samples. This was because water molecules had the etching effect on the polymer chain of the resin, eventually led to the resin hydrolysis and filler/resin interface de-bonding. Finally, the fundamental reason for the degradation of the thermal and mechanical properties of PA6CFEP was that water molecules formed new hydrogen bonds (maximum increase 62.9%) with polymer chains and PA6 fillers, destroying the original cross-linking density of resin in the hygrothermal aging process. The water molecules infiltrated the available space of the resin matrix, leading to a reduction in the inter-chain force of the resin molecules.